Zarządzanie daninami publicznymi w przedsiębiorstwie na przykładzie podmiotu BETA – wybrane aspekty - Milewska, Anna; Maciejczak, Karolina (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2009)
The paper deals with the theoretical and practical aspects of optimization of public levy management in enterprise. The elaboration presents the fundamental definitions from the range of public levy obligations, focusing conducted analysis on taxes. The research included characteristic description of BETA enterprises, the level of tax burden and accessible tools which helped to optimize the public levy value depending on performance specialization of company. The conducted analysis included research of the structure and tax debt dynamic in years 2006–2008. The paper deals also with current decisions and their influence on the level of tax burden, in deprecation aspect based on figures example